2018
DOI: 10.1021/acs.est.7b05443
|View full text |Cite
|
Sign up to set email alerts
|

Radium Sorption to Iron (Hydr)oxides, Pyrite, and Montmorillonite: Implications for Mobility

Abstract: Radium (Ra) is a radioactive element commonly found within soils, sediments, and natural waters. Elevated Ra activities arising through natural and anthropogenic processes pose a threat to groundwater resources and human health, and Ra isotope ratios are used to decipher groundwater movement, estimate submarine discharge flux, and fingerprint contamination associated with hydraulic fracturing operations. Although adsorption to metal (hydr)oxides and certain clay minerals is well established as a dominant mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 49 publications
2
34
0
Order By: Relevance
“…For example, several studies have shown increased mobilization of 226 Ra from clays such as kaolinite and montmorillonite in the presence of a high concentration of NaCl. 45 Here, an increase in the ionic strength of the leaching uid had no pronounced effect on Ra activity in leachates, except for E1 treatment. Compared to low ionic strength treatment, high Ra activity was measured in leachates of E1-ox-Sal-pH7 ( Fig.…”
Section: Bulk Radioactivity and Radium Mobilizationmentioning
confidence: 69%
“…For example, several studies have shown increased mobilization of 226 Ra from clays such as kaolinite and montmorillonite in the presence of a high concentration of NaCl. 45 Here, an increase in the ionic strength of the leaching uid had no pronounced effect on Ra activity in leachates, except for E1 treatment. Compared to low ionic strength treatment, high Ra activity was measured in leachates of E1-ox-Sal-pH7 ( Fig.…”
Section: Bulk Radioactivity and Radium Mobilizationmentioning
confidence: 69%
“…The clay minerals were then collected via centrifugation and washed three times with 1 M NaNO 3 solution to change the clays to a Na + form. Although three washing cycles with NaNO 3 might not be enough to make clay minerals homoionic 47 , this pretreatment was chosen to allow for closer comparisons to previous studies, which determined clay minerals’ Ka and site density through surface complexation modeling 30,44,48 . Excess Na + was removed by washing five times with deionized water, and the final pH was in the range from 6 to 7.…”
Section: Methodsmentioning
confidence: 99%
“…Overall, for the observed cases, the results suggest that there is a risk of drinking water contamination due to radionuclide transport. Although both the weak and strong binding ferrihydrite mineral performed similarly, the result can change depending on the competitive nature of the constituents in the soil, which can be seen in past analyses 22 . A previous study showed that radium levels in Tampa Bay are low.…”
Section: Resultsmentioning
confidence: 85%
“…The amount of abundant minerals in the aquifer can affect the overall remediation process; however it is complex to quantify the amount of potential adsorbents in the soil. From previous studies, a low pH and the presence of other elements and compounds in the solution may induce competition among them, which may then in turn affect the potential of adsorption occurring in the soils 21 , 22 .…”
Section: Discussionmentioning
confidence: 99%